SPECT/CT - solving the dilemma of hepatic hemangioma - Manevska, Nevena; Sinisa Stojanoski; Tanja Makazlieva; Bozhinovska, Nikolina; Daniela Miladinova (My University, 2019)
Hemangiomas, or hemangioma-like appearing lesions, are frequently detected in liver often as an incidental finding on computed tomography (CT) scans. Once detected, they can be a clinical dilemma as they need to be characterized.